Pesantren and the Preservation of Javanese Tradition: A Case Study of Ngalap Berkah in the Sinjang Celebration at Syekh Maulana Ishaq Pesantren, Situbondo - Nuril Anhar, Muhammad; Rif'ah, Rif'ah (JSP: Jurnal Studi Pesantren, 2024)
This study explores how Syekh Maulana Ishaq Islamic Boarding School in Pacarron, Situbondo, preserves the local Ngalap Berkah tradition during the biennial Sinjang celebration, addressing the longstanding historical disconnection between pesantren and Javanese local culture since the polarization following the Diponegoro War in the early 19th century. Employing a qualitative field research design with a cultural anthropological approach, this study utilizes participatory observation, structured in-depth interviews, and documentary analysis to gather empirical data from key informants directly involved in the celebration. The results reveal three core findings. First, the Sinjang celebration is deeply embedded with cultural elements and religious emotions, where participants collectively perceive spiritual blessings within the purification water of Sultan Abdurrahman's sacred garment. Second, the pesantren plays a pivotal role in maintaining Islamic orthodoxy by guiding the community to adhere to Islamic law throughout the tradition, effectively integrating religious values into local practices. Third, the pesantren's motivation for preservation stems from its commitment to Wali Songo's cultural da'wah legacy, the institutionalization of the Barokah concept, and the moral obligation to honor ancestral mandates. This research contributes to understanding how pesantren can successfully reconcile theological commitments with living cultural heritage.